Answer:
Part A: Rewrite the expression by factoring out the greatest common factor. (4 points)
answer:
2y(x³+4x-2x²-8)
Part B: Factor the entire expression completely. Show the steps of your work. (6 points)
answer:
2y(x³+4x-2x²-8)
2y(x³-2x²+4x-8)
2y(x²(x-2)+4(x-2))
2y(x²+4)(x-2)
Answer:
6.57, 6.38, 6.125, 6.057, 6.03, 6.01
The correct answer is
d=50t
Where; d is the distance covered in miles
t is the time taken in hours
The sum of any geometric sequence, (technically any finite set is a sequence, series are infinite) can be expressed as:
s(n)=a(1-r^n)/(1-r), a=initial term, r=common ratio, n=term number
Here you are given a=10 and r=1/5 so your equation is:
s(n)=10(1-(1/5)^n)/(1-1/5) let's simplify this a bit:
s(n)=10(1-(1/5)^n)/(4/5)
s(n)=12.5(1-(1/5)^n) so the sum of the first 5 terms is:
s(5)=12.5(1-(1/5)^5)
s(5)=12.496
as an improper fraction:
(125/10)(3124/3125)
390500/31240
1775/142